Instantaneous monitoring of local fuel concentration in a liquid hydrocarbon-fueled flame using a LIBS plug. (1st December 2017) - Kim, J.H.; Lee, S.H.; Do, H.; Yoh, J.J.
Abstract: A portable device composed of photodiodes and bandpass filters was developed to measure local fuel concentration in a liquid hydrocarbon-fueled spray flame. The plasma emission spectra in and around the flame were selectively captured using such simplified device or plug instead of using a laboratory standard laser-induced breakdown spectroscopy (LIBS) system consisting of an ICCD and a spectrometer. The hydrogen (656 nm) and oxygen (777 nm) atomic lines were selected to determine the fuel concentration in atmospheric pressure. The H/O signal intensity ratio was found to be a strong function of the fuel concentration, and thus a calibration curve for the concentration measurements was established and validated using conventional LIBS. The proposed scheme to measure the local equivalence ratio of spray flames using a bundled layout of multiple LIBS plugs alongside the combustor wall may offer simple and highly robust diagnostics, especially under the harsh combustion conditions within air-breathing engines. Highlights: A plug equipped with photodiodes and bandpass filters is designed. Selective plasma emission detection is utilized using such simple spectroscope. Hydrogen and oxygen signals are selected to determine the local fuel concentration. Multiple plugs support instantaneous performance diagnostics of air-breathing engines.